Social inequalities for student leaders and professional organizations: Florence Nightingale's political legacy - Kênia Lara da Silva; Bruna Dias França; Rafaela Siqueira Costa Schreck; Elen Cristiane Gandra; Letícia Luzia Ferreira Silva (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the nursing systems of understanding and social inequalities from the perspective of student leaders and representatives of nursing professional organizations. Methods: qualitative research supported by the theoretical framework of Marxist dialectics. Threerepresentatives of professional organizations and five student leaders participated in the study. Datawere obtained from individual interviews and submitted to Critical Discourse Analysis. Results: thediscourses are marked by commitment, relational identification and characterize the position of obligation and necessity of nursing in acting with the individuals in situations of inequality, indicating accountability as a social practice. Among the competencies necessary for nursing in confronting social inequalities, political competence is central and is associated with health advocacy. Final Considerations: we conclude that acting on social inequalities is part of the historical construction of nursing. Here, we emphasized the historical importance of Florence Nightingale and her legacy for political action and leadership in nursing.